Factors That Detect Fraud Accounting With Time Pressure As Moderation in Educational Units in Indonesia - Indri Gemi Nestiti; Robin; R. A. Widyanti Diah Lestari (Jurnal Akuntansi, 2025)
Fraud in the field accountancy is actions taken​ Because existence intention or desire For get profit from circumstances , which then result in occurrence manipulation in report finance , as well as practice corruption or abuse assets . The meaning of studies This is evaluate elements that provide impact on fraud accountancy with pressure time as moderating factors in institutions​ education in Indonesia. Approach quantitative implemented as method research , while method survey utilized as method For take sample . Data collected with Distributed 120 questionnaires . Data analysis used the SmartPls program . According to results testing that has been implemented , researchers identify that strength system internal control and values organization influence action cheating accounting . On the other hand , the balance reward as well as personal ethics​ own effect against accounting fraud . Furthermore results other show that pressure time No can moderate variables suitability compensation , ethics personal , efficiency system control , institutional culture to deviation reporting . Based on assessment R2 value , Compensation influence occurrence fraud accounting , ethics individual , effectiveness internal control , as well as culture organization , with pressure time play a role as moderator variables that provide contribution of 21.7%. While 78.3% of the influence from contribution outside .